(untitled) (Feni University Journal, 2026)
The study aims to critically examine the outsourcing of HR activities in the banking sector in Bangladesh. The descriptive and exploratory research was followed, and quantitative primary data were collected from the population of three private and three public commercial banks in Bangladesh. The data were collected from 110 samples using a structured questionnaire and a convenience purposive sampling method. The collected data were analyzed and evaluated using SPSS IBM 25.0. The study revealed that most of the outsourcing service provider firms (90%) are providing “Training and Development” services. This service is customized as per the requirements of the client organizations, and most of the banks outsource HR services and payroll management. The study also found that the most of the reasons for outsourcing are optimization of overhead cost (M=4), making the organization free from the hassle of doing manual work (M=3.9), improving policy and process compliance, a greater extent of functional accuracy (M=3.9), technological advancement (M=3.8), ensures confidentiality (M=3.70), quick response (M=3.6), free from bias (M=3.50). The study again indicated that there is a strong positive correlation between outsourcing HR functions and overall HR performance of the organizations, and regression analysis showed that three HR outsourcing functions significantly contribute to overall HR performance. R-squared (.963) value indicated the linear relationship between the dependent variable (overall HR performance) and independent variable (HR services and payroll, performance Management, recruitment and selection, Training and development). FENI UNIVERSITY JOURNAL, 2025, 4(1), PP. (151-176)